PEMANFAATAN WAKTU DALAM QS. AL-`ASR PERSPEKTIF I’JAZ IQTISHADI - Wildan Setiawan (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
Surah al-‘Asr emphasizes the significance of time according to the Qur’an. Moreover, Surah al-‘Asr teaches important values related to economics, highlighting the utilization of time as a valuable asset. Time is not merely a part of daily routines but also a crucial factor that affects both worldly and spiritual life. Time is highly precious; if not used wisely, it will lead to loss. Time management is depicted as the art of organizing activities efficiently to achieve both worldly and spiritual goals, the findings of this study show that in Surah al-‘Asr, Allah swears by time to underscore the importance of living with faith, doing good deeds, and mutually advising one another in truth and patience. Allah’s oath by time emphasizes that humans are indeed in a state of loss, except for those who have faith, perform good deeds, advise one another in truth, and practice patience. From the perspective of economic miraculousness (I'jaz Iqtishadi), this teaching highlights the significance of business ethics, such as conducting transactions with honesty and fairness and maintaining patience when facing economic challenges. These three elements form the foundation for achieving success and avoiding loss, this analysis also reveals the dimension of economic miraculousness in the principles contained in the Surah, such as the importance of faith in economic transactions conducted with ethics and proper methods. The study concludes, from the perspective of I'jaz Iqtishadi, that the wise use of time will bring benefits and rewards, both in this world and in the hereafter.